DAMPAK SISTEM PEMBELAJARAN ELEKTRONIK TERHADAP HASIL BELAJAR SISWA: SEBUAH STUDI KOMPARATIF DI BERBAGAI TINGKAT PENDIDIKAN - Santia, Prenti; Ainy, Zulfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The impact of electronic learning systems on student learning outcomes is an implementation of technology aimed at assisting the digital learning process and in its implementation requires web-based computer facilities. The use of this technology increases efficiency and effectiveness, transparency, and accountability of learning. This study aims to determine the impact of electronic learning systems on student learning outcomes and a comparative study of E-learning systems at various levels of education. The method used in this study is literature study (library study). The object of this study is electronic learning on student learning outcomes. This study collects data by understanding and studying theories from various literatures. The literature in this study is 20 (twenty) journal articles related to the impact of electronic learning systems on student learning outcomes. The data collection technique used is the secondary data collection technique. The stages in this study are: (1) determining the topic to be reviewed, (2) collecting articles related to the topic, (3) identifying literature, (4) and compiling review articles systematically. Data analysis is carried out with the following steps: data grouping, data presentation, and drawing conclusions. The results of this study indicate that the impact of the electronic learning system on student learning outcomes is a positive and negative increase, but with different variations at each level of education.